Generalized keratosis pilaris induced by testosterone injections in a patient with CHARGE syndrome (Dermatology Reports, 2023)
Keratosis pilaris (KP) is a common disorder of follicular keratinization characterized by keratotic follicular papules with varying degrees of perifollicular erythema. Keratosis pilaris affects up to half of normal children and up to three-quarters of children with atopic dermatitis. KP is prominent during adolescence and less common in older people, but it may occur in children and adults of all ages. In this report, we describe the case of a 13-year-old boy known to have CHARGE syndrome who developed generalized keratosis pilaris after testosterone injections. To the best of our knowledge, this is the first reported case of generalized keratosis pilaris induced by testosterone injection.